2019
DOI: 10.1021/acs.inorgchem.9b00028
|View full text |Cite
|
Sign up to set email alerts
|

Tuning of the Compositions and Multiple Activator Sites toward Single-Phased White Emission in (Ca9–xSrx)MgK(PO4)7:Eu2+ Phosphors for Solid-State Lighting

Abstract: Manipulating the distribution of rare earth activators in multiple cations’ sites of phosphor materials is an essential step to obtain tunable emission for the phosphor-converted white-light-emitting diodes (pc-WLEDs). However, it remains the challenge to realize the photoluminescence tuning in the single-phased phosphor with single activator, due to the uncertain location of doped ions and adjustable crystallographic sites. Herein we reported the β-Ca3(PO4)2-type solid solution phosphors (Ca8.98–x Sr x )­MgK­… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(38 citation statements)
references
References 32 publications
0
38
0
Order By: Relevance
“…Among them, the Ca(5) site was unstable compared with other cation sites, so this site was usually empty 14‐16 . For a long time, as an important host materials, the β‐Ca 3 (PO 4 ) 2 and derivatives have been widely investigated for applications in various fields, such as ferroelectric ceramic materials, upconversion luminescence, white light‐emitting diodes, CT/MRI multimodal imaging, and so on 17‐19 . In 1996, Lazoryak et al reported a metal Fe‐contained compound Ca 9 Fe(PO 4 ) 7 with β‐Ca 3 (PO 4 ) 2 structure for the first time 20 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among them, the Ca(5) site was unstable compared with other cation sites, so this site was usually empty 14‐16 . For a long time, as an important host materials, the β‐Ca 3 (PO 4 ) 2 and derivatives have been widely investigated for applications in various fields, such as ferroelectric ceramic materials, upconversion luminescence, white light‐emitting diodes, CT/MRI multimodal imaging, and so on 17‐19 . In 1996, Lazoryak et al reported a metal Fe‐contained compound Ca 9 Fe(PO 4 ) 7 with β‐Ca 3 (PO 4 ) 2 structure for the first time 20 .…”
Section: Introductionmentioning
confidence: 99%
“…[14][15][16] For a long time, as an important host materials, the β-Ca 3 (PO 4 ) 2 and derivatives have been widely investigated for applications in various fields, such as ferroelectric ceramic materials, upconversion luminescence, white light-emitting diodes, CT/MRI multimodal imaging, and so on. [17][18][19] In 1996, Lazoryak et al reported a metal Fe-contained compound Ca 9 Fe(PO 4 ) 7 with β-Ca 3 (PO 4 ) 2 structure for the first time. 20 The doping of Fe 3+ ions can not only control the phase composition and crystallinity, but also introduce magnetic and ferroelectric property owing to the unpaired 4f electrons of Fe 3+ ions.…”
mentioning
confidence: 99%
“…White light emitting diode light source with a low driving voltage, applicability, high stability, short response time, mercury and lead pollution, monochromatic light etc., will be the most promising lightning source, which will replace the incandescent, uorescent, high intensity gas discharge lamp in the 21 century [1,2]. Currently people use blue LED chip coated with yellowish phosphor of YAG to achieve white LED, its color temperature is usually higher than 5000K, the general color rendering index also is less than 80.…”
Section: Introductionmentioning
confidence: 99%
“…Increasingly, in recent years, researchers have synthesized series of phosphors with different colour and white luminescence characteristics by doping different rare earth ions and using phosphate as the substrate. [9][10][11][12] In 1911, Van Klooster synthesized M 2 BPO 5 (M = Na, K) using a high-temperature solid-phase method [13] and provided a theoretical basis for the synthesis of boron phosphate. Berezovskaya and colleagues [14] found that the basic absorption band of the main lattice was caused by anion group transition and that the SrBPO 5 :Ce 3+ system had good stability when compared with the vacuum ultraviolet (VUV) excitation spectra of MBPO 5 :Ce 3+ (M = Ca, Sr, Ba).…”
Section: Introductionmentioning
confidence: 99%